Deficiency of IL12p40 (Interleukin 12 p40) Promotes Ang II (Angiotensin II)–Induced Abdominal Aortic Aneurysm. Issue 2 (February 2019) - Sharma, Neekun; Dev, Rishabh; Belenchia, Anthony M.; Aroor, Annayya R.; Whaley-Connell, Adam; Pulakat, Lakshmi; Hans, Chetan P.
Abstract : Objective—: Abdominal aortic aneurysm is caused by the accumulation of inflammatory cells in the aortic wall. Our recent studies demonstrated that inhibition of Notch signaling attenuates abdominal aortic aneurysm formation by shifting the macrophage balance towards anti-inflammatory (M2) phenotype. Using IL12p40 −/− (interleukin 12 p40) mice, we investigated the effects of M2-predominant macrophages on the development of abdominal aortic aneurysm. Approach and Results—: Male (8–10 week-old) wild-type and IL12p40 −/− mice (n=15) on C57BL/6 background were infused with Ang II (angiotensin II, 1000 ng/kg per minute) by implanting osmotic pumps subcutaneously for 28 days. In the IL12p40 −/− mice, Ang II significantly increased the maximal intraluminal diameter (9/15) as determined by transabdominal ultrasound imaging. In addition, IL12p40-deletion significantly increased aortic stiffness in response to Ang II as measured by pulse wave velocity and atomic force microscopy. Histologically, IL12p40 −/− mice exhibited increased maximal external diameter of aorta and aortic lesions associated with collagen deposition and increased elastin fragmentation compared with wild-type mice infused with Ang II. Mechanistically, IL12p40 deficiency by siRNA (small interfering RNA) augmented the Tgfβ2 -mediated Mmp2 expression in wild-type bone marrow–derived macrophages without affecting the expression of Mmp9 . No such effects of IL12p40 deficiency on MMP2/MMP9 was observed in human aortic smooth muscle cells or fibroblasts. Depletion of macrophages in IL12p40 −/− mice by clodronate liposomes significantly decreased the maximal external diameter of aorta and aortic stiffness in response to Ang II as determined by imaging and atomic force microscopy. Conclusions—: IL12p40 depletion promotes the development of abdominal aortic aneurysm, in part, by facilitating recruitment of M2-like macrophages and potentiating aortic stiffness and fibrosis mediated by Tgfβ2 . Abstract : Supplemental Digital Content is available in the text.